10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
This study aims to analyze the relationship between maternal knowledge and attitudes and maternal behavior in caring for stunted children aged 24-35 months. Additionally, it examines how demographic variables are related to these independent variables. A cross-sectional study design was employed, focusing on mothers of stunted children aged 24-35 months in an area of a developing country (n = 56). We utilized a modified version of a previous knowledge and attitude assessment tool. The instrument measuring maternal behavior in caring for stunted children remained unmodified. The study commenced in April 2025, following the acquisition of ethical approval. Data collection included demographic questionnaires, respondent identity forms, informed consent, knowledge assessments, attitude surveys, and evaluations of maternal behavior regarding the care of stunted children. The analysis revealed no significant relationship between maternal knowledge and behavior in caring for stunted children (p = 0.268; p > 0.05). However, there was a significant positive correlation between maternal attitudes and maternal behavior (p = 0.000; p < 0.05). As maternal knowledge decreases, the behavior of caring for stunted children tends to improve. Conversely, an increase in knowledge correlates with a decrease in caring behavior. On the other hand, an increase in positive attitudes towards caring for stunted children leads to an improvement in maternal behavior, while a decrease in attitudes results in poorer care behavior. Behaviors related to caring for stunting include four essential domains, which can serve as a framework for independent assessments of mothers caring for stunted children aged 24-35 months.